2017
DOI: 10.1007/s12223-017-0559-y
|View full text |Cite
|
Sign up to set email alerts
|

Four Saccharomyces species differ in their tolerance to various stresses though they have similar basic physiological parameters

Abstract: Saccharomyces species, which are mostly used in the food and beverage industries, are known to differ in their fermentation efficiency and tolerance of adverse fermentation conditions. However, the basis of their difference has not been fully elucidated, although their genomes have been sequenced and analyzed. Five strains of four Saccharomyces species (S. cerevisiae, S. kudriavzevii, S. bayanus, and S. paradoxus), when grown in parallel in laboratory conditions, exhibit very similar basic physiological parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Both of these solutes are not toxic to yeast cells, and other Saccharomyces species support even higher concentrations (Zemancikova et al . ). This osmosensitivity is probably not due to a diminished ability to produce the necessary amount of glycerol upon osmotic stress, as S. kudriavzevii cells produce a substantial amount of glycerol even without stress, and this amount increases upon stressful conditions (Perez‐Torrado et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Both of these solutes are not toxic to yeast cells, and other Saccharomyces species support even higher concentrations (Zemancikova et al . ). This osmosensitivity is probably not due to a diminished ability to produce the necessary amount of glycerol upon osmotic stress, as S. kudriavzevii cells produce a substantial amount of glycerol even without stress, and this amount increases upon stressful conditions (Perez‐Torrado et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Zemancikova et al . ). These results indicated that although a lot of glycerol is produced, the ability of cells to retain it in the cytosol is not sufficient.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, more information has become available, for example, to identify specific genes involved in the drying tolerance of yeast strains (Sasano, Takahashi, Shima, & Tagaki, ; Shima & Tagaki, ). Stress‐tolerant strains would be able to quickly accommodate their cell size and metabolism (Zemančíková, Kodedová, Papoušková, & Sychrová, ). Takagi () has written a very complete review on challenges in the development of yeast strains with improved stress tolerance.…”
Section: Strains: Baker's Yeastmentioning
confidence: 99%